ANALISA DESAIN KARAKTER PADA KOMIK “NUSA FIVE” - Octavianus Bramantha (Narada : Jurnal Desain dan Seni, 2020)
In the development of the digital world today, comics have become one of the most rapidly developing works of art, because the increasingly depleted problem of comic artists in publishing their work, many new comic artists have sprung up abroad and in the country. It is "Nusa Five" which is the latest work from Sweta Kartika. The comic that combines the theme of enriching the Japanese superhero team with the cultural elements of the archipelago becomes a fresh style in the world of Indonesian comics. In this research, the author aims to analyze the character design found in the "Nusa Five" comic.